2016
DOI: 10.1016/j.mam.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

O 2 sensing, mitochondria and ROS signaling: The fog is lifting

Abstract: Mitochondria are responsible for the majority of oxygen consumption in cells, and thus represent a conceptually appealing site for cellular oxygen sensing. Over the past 40 years a number of mechanisms to explain how mitochondria participate in oxygen sensing have been proposed. However, no consensus has been reached regarding how mitochondria could regulate transcriptional and post-translational responses to hypoxia. Nevertheless, a growing body of data continues to implicate a role for increased reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 148 publications
(156 reference statements)
4
125
0
5
Order By: Relevance
“…The authors used the fluorescent dye 29,79-dichlorofluorescin (DCF), which indicated pronounced ROS production when cells were shifted from normoxic (21% O 2 ) to hypoxic (2% O 2 ) conditions, which they attributed to superoxide production at complex III using mETC inhibitors. While controversies persist, mtROS are now widely considered a potential early trigger in the mammalian transcriptional response to low oxygen (Bailey-Serres and Chang, 2005;Waypa et al, 2016). Whether, however, superoxide itself has a role as trigger remains challenging to answer.…”
Section: Which Molecules Qualify As Upstream Mitochondrial Signals? Rmentioning
confidence: 99%
“…The authors used the fluorescent dye 29,79-dichlorofluorescin (DCF), which indicated pronounced ROS production when cells were shifted from normoxic (21% O 2 ) to hypoxic (2% O 2 ) conditions, which they attributed to superoxide production at complex III using mETC inhibitors. While controversies persist, mtROS are now widely considered a potential early trigger in the mammalian transcriptional response to low oxygen (Bailey-Serres and Chang, 2005;Waypa et al, 2016). Whether, however, superoxide itself has a role as trigger remains challenging to answer.…”
Section: Which Molecules Qualify As Upstream Mitochondrial Signals? Rmentioning
confidence: 99%
“…In this case, cellular respiration is an important source of ROS (Waypa et al, 2016). Accordingly, ROS role in the development of PH is strongly suggested by studies showing profound alteration in mitochondrial structure and function in that context.…”
Section: Reactive Oxygen Species and Pulmonary Hypertensionmentioning
confidence: 99%
“…− ) from complex III to the intermembrane space, where it is converted to hydrogen peroxide (H 2 O 2 ) by superoxide dismutase (Thompson, 2016, Waypa et al, 2016). The H 2 O 2 then enters the cytosol, where it activates multiple responses contributing to smooth muscle contraction and remodeling.…”
Section: Reactive Oxygen Species and Pulmonary Hypertensionmentioning
confidence: 99%
“…It is anticipated that compaction will further differentiate the two environments such that the inner cells find themselves in a more hypoxic environment. It is becoming clear that mammalian cells sense hypoxia through mitochondria's ETCs' generation of ROS, which acts as a signaling molecule to initiate the hypoxic response (Waypa, Smith, & Schumacker, 2016). Could one key to TE differentiation be ROS signaling by more hypoxic inner cells, which serves as a trigger to activate a TE differentiation pathway in the outer cells, leading to changes in mitochondrial morphology in the outer cells?…”
Section: Perspective and Future Considerationsmentioning
confidence: 99%